Avatars Going Mainstream: Typology of Tropes in Avatar-Based Storytelling Practices - Tymińska, Marta (Replay. The Polish Journal of Game Studies, 2017)
Due to the growing popularity of video games, gaming itself has become a shared experience among media audiences worldwide. The phenomenon of avatar-based games has led to the emergence of new storytelling practices. The paper proposes a typology of tropes in these avatar-based narratives focusing on non-game case studies. Suggested tropes are also confronted with the latest research on avatars in the area of game studies and current knowledge of the issues concerning the player-avatar relationship. Some of the most popular misconceptions regarding the gameplay experience and its representation in non-game media are exposed as a result of this analysis. The research confirms that popular culture perceives gaming experience as closely related to the player identity, as the latter inspires new genres of non-game narratives.